Kerjasama Pemerintah Kabupaten Jepara Dengan Pihak Swasta Dalam Pengambangan Tenun Troso - Riswandha Imawan; Priyatno Harsasto; Muhammad Adnan (Journal of Politic and Government Studies, 2014)
AbstractTroso weaving industry is one industry that is the mainstay of Jepara districtnow being developed to be the backbone of the economy in the region, especiallyin the district of Jepara. In the development of this troso woven Jepara DistrictGovernment through the Department of Trade and Industry in cooperation withthe private sector in this regard and ASEPHI UNISNU. Department of Industryand Trade in cooperation with UNISNU in terms of training, and also cooperatewith ASEPHI in terms of promotion and marketing.This study analyzed the cooperation between the Government of Jeparathrough the Department of Industry and Trade with UNISNU and ASEPHI trosostarted weaving in the development of this form of cooperation, theimplementation of the cooperation, the result of the collaboration, and the benefitsof cooperation are carried out. In conducting this study, researchers used aqualitative research method that will generate descriptive date. This research wasconducted in the district of Jepara. Researchers obtained data from documents,observations, and interviews.From these results, it was found that the form of cooperation carried out bythe Department of Industry and Trade with UNISNU is a design innovationtraining and motifs, and forms of cooperation conducted by the Department ofIndustry and Trade is an exhibition ASEPHI. The implementation of cooperationusing a feedback mechanism between the Department of Industry and Trade withUNISNU and ASEPHI, and coordination strategy using mutual adjustment. Theresults of this collaboration is done weaving troso HPI increased capacity,increased access to promotion and marketing, and the value of production andturnover of artisans and entrepreneurs increase. The troso weaving artisans andentrepreneurs also benefit from this cooperation is that they become more variedin making early design motifs, and also the area of marketing their products is alsoincreasingly widespread.Keywords: cooperation, development, Weaving Troso